Uma crítica pós-Keynesiana à meta de PIB nominal - Brazil, Hugo Leonardo Salgado (2015)
The monetary policy mainstream encourages the use of rules of economic policy in order to avoid time inconsistency problems and ensure inflation control. Throughout history, various types of monetary regimes were implemented, as in the case of Exchange Rate Targeting and Monetary Targeting. Currently, countries among them, New Zealand, Spain, United Kingdom, Canada, Sweden use the Inflation Targeting, which is to ensure an inflation rate set by the monetary authority achieved through a policy instrument, in the case, short-term nominal interest rate. The fall of Lehman Brothers and AIG in September 2008 triggered a deep financial crisis worldwide with rapid drop in economic activity, especially in european countries and the USA. In this scenario, most central banks came following the prescriptions imposed by the dominant theory in a process of reducing nominal interest rate. However, when the policy instrument reached its zero lower bound, the monetary policy stance has become limited, making the monetary authorities adopt unconventional methods try to leverage the economy. With the lessons that the crisis imposed on dominant theory, an internal critique has resurrected (the subject is studied since the late 1970’s) the proposed monetary regime change in favor of Nominal GDP Targeting. Mainstream authors such as Krugman (2011), Romer (2011) and Frankel (2013) among others, regard regime change as the best way to get the economy to replace pre-crisis levels. With regard to external review, post-keynesians do several criticism of the monetary policy adopted by the New Synthesis, especially Inflation Targeting. However, there is a literature that makes the theoretical critique of Nominal GDP Targeting. Thus, the aim of this work is provide, within the heterodox theory, theoretical criticism of Nominal GDP Targeting, starting from post-keynesian concepts such as non-neutrality of money, the role of central banks, the importance of investment and endogenous potential output on the demand side. The criticism concerns the use of potential output determined by the supply side, which makes the Nominal GDP an extension of Inflation Targeting, the Central Bank's actions limitation to stimulate investment and change productive capacity of the economy and the irreversibility of time compared to "historical dependence" proposed by a kind of Meta Nominal GDP. If Central Bank has unorthodox characteristics, Nominal GDP can ensure higher gains from product due to their greater flexibility, especially in the case of supply shocks.